2021
DOI: 10.1007/s42452-020-04011-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water quantity–quality, floodplain landuse, and land surface temperature (LST) of Turag River in Bangladesh: an integrated approach of geospatial, field, and laboratory analyses

Abstract: Rapid urbanization, industrialization, and development activities are posing numerous threats to the rivers of Bangladesh. In the recent decade, Turag River has been exposed to severe threats due to anthropogenic activities. The present research deals with the evaluation of water quantity–quality, landuse and landcover (LULC), and land surface temperature (LST) of Turag River and its floodplain by using an integrated approach of field study, laboratory analysis, and geospatial techniques. LULC mapping of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The respondents (12.9%) also recognized the use of river water in industries to operate machinery and cool it down as one of the most important causes of river pollution, as this nasty water, which includes chemical composition, is subsequently discharged back into the river (Observation; Photograph 1b) ended up with increasing river water temperature. The work of Tania et al (2021) confirmed that the excessive temperature of river surface water was due to the discharge of hot wastewater from industrial sources besides the Turag River. The respondents considered this factor as another cause of river pollution as the water used for cooling is warmer than the river water at normal temperature.…”
Section: Discharge From Industriesmentioning
confidence: 79%
See 1 more Smart Citation
“…The respondents (12.9%) also recognized the use of river water in industries to operate machinery and cool it down as one of the most important causes of river pollution, as this nasty water, which includes chemical composition, is subsequently discharged back into the river (Observation; Photograph 1b) ended up with increasing river water temperature. The work of Tania et al (2021) confirmed that the excessive temperature of river surface water was due to the discharge of hot wastewater from industrial sources besides the Turag River. The respondents considered this factor as another cause of river pollution as the water used for cooling is warmer than the river water at normal temperature.…”
Section: Discharge From Industriesmentioning
confidence: 79%
“…Multi-spectral satellite data has identified rapid conversion from agricultural cultivated land to urban land uses along the Turag-Tongi basin over the last few decades (Dewan et al, 2012;Dewan and Yamaguchi, 2009). However, the study by Tania et al, 2021;Hassan et al, 2019;Zaman et al, 2018;Saha et al, 2016;Guttikunda et al, 2013, etc. confirmed that local land uses are correlated with the deterioration of Turag River water quality.…”
Section: Land Use For Other Purposesmentioning
confidence: 99%
“…The area in which this research work was conducted is also known as "Tongi Heavy Industrial Area". For the last few decades there has been incredible industrial influx and development near the periphery of the Turag River and thus due to immense discharge of industrial effluents the water quality of this river has been severely degraded [28]. The Turag River has been avowed as one of the "Ecologically Critical Areas (ECA)" of this country by the Department of Environment Bangladesh [29].…”
Section: Study Areamentioning
confidence: 99%
“…In addition, insufficient monitoring and law enforcement by government officials were recorded in textile companies. Prioritize the execution of the existing laws and effective governance including all stakeholders in order to ensure improved water sources for all[28,15]. It is necessary to ensure the prevention of illegal encroachment, the marking of river channel borders, and the dredging of severely narrow and shallow riverbeds.…”
mentioning
confidence: 99%
“…By providing timely and synoptic views of land-based coverage, remote sensing images more suitable for monitor NDVI, NDWI, and NDBI [19], [20], [21], [22]. types and times [23], [24], [25], [26], [27], [28] [29], [30], [31], [32]. There are various methods for measuring the LST by using field measurements, but that's very complex and expensive.…”
Section: Introductionmentioning
confidence: 99%